1998
DOI: 10.1103/physreve.58.1494
|View full text |Cite
|
Sign up to set email alerts
|

Gutenberg-Richter and characteristic earthquake behavior in simple mean-field models of heterogeneous faults

Abstract: The statistics of earthquakes in a heterogeneous fault zone is studied analytically and numerically in a mean field version of a model for a segmented fault system in a three-dimensional elastic solid [1,2]. The studies focus on the interplay between the roles of disorder, dynamical effects, and driving mechanisms. A two-parameter phase diagram is found, spanned by the amplitude of dynamical weakening (or "overshoot") effects ǫ and the normal distance L of the driving forces from the fault. In general, small ǫ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
163
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 20 publications
(34 reference statements)
14
163
3
Order By: Relevance
“…For example, constitutive mechanical rules are used which are known to be much simpler than those implied by the observation of rate and state dependence of frictional slip in laboratory sliding experiments [Deiterich, 1979]. However, we have seen that the scaling properties of other near-critical systems are robust with respect to the details of the assumed local dynamics.…”
Section: Self-organized Criticalitymentioning
confidence: 98%
See 1 more Smart Citation
“…For example, constitutive mechanical rules are used which are known to be much simpler than those implied by the observation of rate and state dependence of frictional slip in laboratory sliding experiments [Deiterich, 1979]. However, we have seen that the scaling properties of other near-critical systems are robust with respect to the details of the assumed local dynamics.…”
Section: Self-organized Criticalitymentioning
confidence: 98%
“…Using the same model, Ceva [1995] showed that the nature of quenched disorder can have a strong effect on the observed behavior, with point defects having more impact than more extended heterogeneities. Dahmen et al [1998] examined the behavior of a three-dimensional dynamic earthquake model including inertial terms, and calculated the position of the phase boundary between a "small earthquake" phase with a finite correlation length and a "metastable" phase with large characteristic earthquakes, depending on the values of the characteristic cut off size and the slipweakening amplitude. Their model predicts a first-order phase transition between the two phases, in the sense that there is a finite gap between the size of the largest events and the rest of the population.…”
Section: Self-organized Criticalitymentioning
confidence: 99%
“…The magnitude of the stochastic term must overcome this deficit for a rupture to propagate. A previous approach [8] is to linearize the stress excess about κ = 0 (not including terms of and compute the first crossings of the random walk with the line. The exact result is given by the Bachelier-Levy formula [17].…”
Section: A Event Size Distributionsmentioning
confidence: 99%
“…However, the limiting case of mean-field models are beginning to yield to analytical understanding [8,9,10,11]. Mean field model simulations exhibit complex event histories and regimes of behavior, including a power law magnitude-frequency relation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation